Unique carbohydrate binding platforms employed by the glucan phosphatases - Emanuelle, Shane (Cell Mol Life Sci, 2016)
Glucan phosphatases are a family of enzymes that are functionally conserved at the enzymatic level in animals and plants. These enzymes bind and dephosphorylate glycogen in animals and starch in plants. While the enzymatic function is conserved, the glucan phosphatases employ distinct mechanisms to bind and dephosphorylate glycogen or starch. The founding member of the family is a bimodular human protein called laforin that is comprised of a carbohydrate binding module 20 (CBM20) followed by a dual specificity phosphatase domain. Plants contain two glucan phosphatases: Starch EXcess4 (SEX4) and Like Sex Four2 (LSF2). SEX4 contains a chloroplast targeting peptide, dual specificity phosphatase (DSP) domain, a CBM45, and a carboxy-terminal motif. LSF2 is comprised of simply a chloroplast targeting peptide, DSP domain, and carboxy-terminal motif. SEX4 employs an integrated DSP-CBM glucan-binding platform to engage and dephosphorylate starch. LSF2 lacks a CBM and instead utilizes two surface binding sites to bind and dephosphorylate starch. Laforin is a dimeric protein in solution and it utilizes a tetramodular architecture and cooperativity to bind and dephosphorylate glycogen. This chapter describes the biological role of glucan phosphatases in glycogen and starch metabolism and compares and contrasts their ability to bind and dephosphorylate glucans.